Edwin Ndibalema, Agriculture Enterpreneur, Tanzania - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2020)
Edwin Ndibalema from Tanzania shares his story on youth engagement in Agriculture with IITA celebrating International Youth Day.